Virus as a Nanocarrier for Drug Delivery Redefining Medical Therapeutics - A Status Report - Ojha, Sanjay K.; Pattnaik, Ritesh; Singh, Puneet Kumar; Dixit, Shubha; Mishra, Snehasish; Pal, Sreyasi; Kumar, Subrat (Combinatorial Chemistry & High Throughput Screening, 2022)
Over the last two decades, drug delivery systems have evolved at a tremendous pace. Synthetic nanoparticles have played an important role in vaccine design and delivery as these have shown improved safety and efficacy over conventional formulations. Nanocarriers formulated by natural, biological building blocks have become an important tool in biomedicine. A successful nanocarrier must possess specific properties like evading the host immune system, target specificity, cellular entry, escape from endosomes, and the ability to release the active material into the cytoplasm. The virus can perform some or all of these functions, making it a suitable candidate as a naturally occurring nanocarrier. Viruses could be made non-infectious and non-replicative without compromising their ability to penetrate cells, making them useful for a vast spectrum of applications. Currently, many such carrier molecules as bio-nanocapsules are at various development stages. This review covers the advances in the field of viruses as potential nanocarriers and discusses the related technologies and strategies to target specific cells by using virus-inspired nanocarriers. These virus-based nanocarriers could provide solutions to address pressing and emerging concerns in infectious diseases in the future.
Keywords: synthetic nanoparticles